Smart Measurement Technique Employed for Detection of Localized Anomalies in the Atmosphere. (2020) - Bhattacharya, Shourabh; Agarwal, Anupma; Sikarwar, Manju; Mishra, Pankaj
Abstract: Atmospheric electricity and global electric circuit have been one of most important segments under investigation in recent times. For years, despite the various studies performed using various techniques on atmospheric parameters, it has now gradually become inevitable to use miniaturized circuits and compact instrumentation system to analysis the dynamics of the atmosphere. One such 'Smart Measurement Technique' is the use of the Electric Field Mill to measure and detect the lower atmospheric field under the case of perturbed state. In this paper, authors have discussed the effective implementation of the compact electric field mill which may be termed as a Smart way to measure the parameters. In the process some sample results have also been presented to reflect upon the effectiveness of the experimentation system